Evaluasi Aspek Finansial IPAL Komunal (Studi: Kota Malang Provinsi Jawa Timur) - I Made Satya Graha; Edya Pitoyo; I Kadek Ardi Putra (Program Studi Teknik Lingkungan Unmas Denpasar, 2022)
In this study, samples will be taken from 6 Communal WWTP locations in the City of Malang. Based on the review of Communal IPAL by DEWATS, the majority of IPAL Communal is not monitored, so it is necessary to evaluate evaluation on the ability and willingness of the community to care for WWTPs Communal with operating costs according to SOP. Based on the results of the evaluation of the financial aspect, the willingness of residents to pay fees between 2000 rupiahs to 5000 rupiahs and the ability of residents to pay at the Tlogomas Communal IPAL is Rp. 11,150, Oro - Oro Dowo Rp. 7,125, Jodipan Rp. 8,900, Kota Lama Rp. 8,750, Mergososo Rp. 6,150, and Gadang Rp. 8,900.